Evaluation Of Physicochemical Separation Characteristics of Pig Manure According to the Type of Solid-Liquid Separator Processes - Kim, Sooryang; Park, Seunghyun; Lee, Suchan; Jung, Jiwon; Ahn, Sanghyean; Ham, Kwonwoong; Lee, Myunggyu (Journal of Agronomy Research, 2023)
Objectives The solid-liquid separation (SLS) process generally separates solid and liquid fractions in wastewater and livestock manure. The solid-liquid separation process is an essential pretreatment step for the recycling and purification of pig manure. This study has assessed the separation and/or reduction efficiency by various SLS processes used in pig farms. Methods Seven types of SLS processes (centrifuge, centrifuge (+coagulation agent), belt press (+ coagulation agent), drum screen, inclined screen, vibration screen, and screw press) were used on 11 pig farms and conducted a comparative analysis. As for the sample in this study, the pig raw manure before treatment, the separated liquid and solid manure after treatment of the SLS process collected, respectively. These samples were provided for pH, EC(electrical conductivity) moisture content, CODMn, BOD5, TN, TP, K, TS, SS, NaCl, and heavy metals analysis. Results and Discussion The belt press (+coagulation agent) process had the highest TS and SS reduction rate of 78.8% and 96.9%, respectively. The highest removal efficiency of TN and TP was41.0% and 94.2% by belt press (+coagulation agent) and centrifuge (+coagulation agent),respectively. The belt press (+coagulation agent) removed 59.4% and 66.0% of BOD5 and CODMn,respectively. The Zn and Cu were removed 100% and 98.6% by centrifuge (+coagulation agent).However, the drum screen, inclined screen, vibration screen, screw press, and centrifuge showed lower removal efficiency of nutrient contents, solids, Zn, and Cu than centrifugal and belt press processes with chemical coagulation. Conclusions The centrifugal and belt press separation processes that used chemical coagulation showed much more removal efficiency of nutrient contents, solids, and metals like Zn and Cu. Although SLS with chemical coagulants is an effective pre-treatment process for liquid manure treatment and helps removal effect for suspended solids, nutrients, and heavy metals, further studies are needed on how it affects biological or chemical processing processes that are linked.
Keywords: livestock; pig manure; solid–liquid separations